Targeted Therapy With PI3K and FGFR Inhibitors on Human Papillomavirus Positive and Negative Tonsillar and Base of Tongue Cancer Lines With and Without Corresponding Mutations - Holzhauser, Stefan; Wild, Nicole; Zupancic, Mark; Ursu, Ramona G.; Bersani, Cinzia; Näsman, Anders; Kostopoulou, Ourania N.; Dalianis, Tina (Frontiers in Oncology, 2021)
Objectives Human papillomavirus positive (HPV+) tonsillar and base of tongue squamous cell carcinoma (TSCC/BOTSCC), the major subsites of oropharyngeal squamous cell carcinoma (OPSCC) have favorable outcome, but upon relapse, outcome is poor and new therapies needed. Since, phosphatidyl-inositol-4,5-bisphosphate 3-kinase, catalytic subunit alpha (PIK3CA) and fibroblast-growth-factor-receptor-3 (FGFR3) mutations often occur in such tumors, here, we tested targeted therapy directed to such genes in TSCC/BOTSCC cell lines. We also combined the two types of inhibitors with each other, and cisplatin or docetaxel that are used clinically. Methods The HPV+ CU-OP-2, -3, -20, UPCI-SCC-154, and HPV- CU-OP-17 and UT-SCC-60A cell lines were first tested for common PIK3CA/FGFR3 mutations by competitive-allele-specific TaqMan-PCR. They were then treated with the food and drug administration (FDA) approved drugs, alpelisib (BYL719) and erdafitinib (JNJ-42756493) alone and in combination with cisplatin or docetaxel. Viability, proliferation, apoptosis and cytotoxicity responses were thereafter followed by WST-1 assays and the IncuCyte S3 Live® Cell Analysis System. Results HPV+ CU-OP-2 had a pS249C-FGFR3, and like CU-OP-20, a pE545K-PIK3CA mutation, while no other lines had such mutations. Irrespectively, dose dependent responses to all PI3K/FGFR inhibitors were obtained, and upon combining the inhibitors, positive effects were observed. Cisplatin and docetaxel also induced dose dependent responses, and upon combination with the inhibitors, both positive and neutral effects were found. Conclusions The data suggest that FDA approved drugs alpelisib and erdafitinib efficiently inhibit TSCC/BOTSCC cell line growth, especially when combined irrespective of presence of corresponding mutations and should be further explored, for use upon recurrent disease.